A contemporary guide to economics, peace, and laughter - Galbraith, John Kenneth (Boston: Houghton Mifflin, 1971)
The book covers Economics, Peace and the rest of the world, Contemporaries and amusements and Points of a compass.
Cover title: Economics, peace, and laughter.
Includes index
rpm 22/06/2017
Loans
Keywords: Economics; Economics -- Philosophy; United States -- Economic conditions; United States -- Social conditions; United States